Eksistensi Densus 88: Analisis Evaluasi Dan Solusi Terkait Wacana Pembubaran Densus 88 - Zainal Muhtar (UIN Sunan Kalijaga Yogyakarta, 2014)
Corruption was considered detrimental to social and economic rights ofIndonesian society that is an extra-ordinary crime and a common enemy Indonesiansociety and the nation as a whole. Therefore, necessary extra-ordinary enforcement andextra-ordinary measures anyway. One such action is to conduct a comprehensive shift tothe existing verification system, by applying the reversal of burden of proof (omkeringvan bewijslast) in PTPK Act. The application of this principle tends to cause the shiftof the presumption of innocence to the presumption of guilt, whereas protection andrespect for Human Rights defendant can not be reduced at all and for any reason (nonderogable right). This paper attempts to examine the application of the reversal of theburden of proof (omkering van bewijslast) in the theoretical study and practice, to find atheoretical justification for the application of the reversal of the burden of proof inrelation to human rights perspective defendant.